Analysis of the Impact of Technological Disruption on the Economic Behavior of Homo Islamicus Consumers in Generation Z - Manik, Raudah Uci Mayasari; Harahap, Isnaini; Atika, Atika (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Generation Z, the largest consumer group in the world including Indonesia, will play an active role in consumption trends over the next thirty years. This study aims to analyze how economic technological disruption affects the consumption behavior of Homoislamicus among Gen Z. The research employed a quantitative approach with an online questionnaire distributed to 267 Gen Z respondents at the Al-Ikhlas Dairi Islamic College. Data analysis utilized simple linear regression to test the relationship between technological disruption and Homoislamicus behavior. The findings indicate that economic technological disruption significantly influences the consumption behavior of Gen Z individuals identifying as Homoislamicus at Al-Ikhlas Dairi Islamic College. Regression analysis shows that increased economic technological disruption positively contributes to Gen Z consumption behavior, with a coefficient of 0.357. However, only approximately 11.7% of the variation in Homoislamicus behavior can be explained by this variable, underscoring the importance of further research to understand other factors influencing Gen Z consumption patterns.